KUALITAS SUMBER DAYA MANUSIA DITINJAU DARI TINGKAT PENDIDIKAN, PELATIHAN KERJA DAN PENGALAMAN KERJA DI BALAI LATIHAN KERJA (BLK) TECHNOPARK GANESHA SUKOWATI SRAGEN - Mei Anjarwati; Bambang Mursito; Sarsono Sarsono (JURNAL ILMIAH EDUNOMIKA, 2020)
This aims to find out the effect based on the simultaneously and partially method in the observation of education level, job training, and work experience in Balai Latihan Kerja (BLK) Technopark Ganesha Sukowati Sragen. Furthermore, this research also aims to know, are the training participants, after doing the training in Balai Latihan Kerja (BLK) Technopark Ganesha Sukowati Sragen able to get a job. The design of this research is descriptive quantitative. The entire population is used as the sample, there are 53 respondents, by using the saturation sampling technique. Retrieval of the data is using questionnaires. The analysis technique that used is multiple linear regressions. The result of this research explains that the F-test in educational level, job training, and work experiences simultaneously and significantly affect the quality of human resources of participants in Balai Latihan Kerja (BLK) Technopark Ganesha Sukowati Sragen. The T-test result explains that the level of education, job training, and work experiences partially have a positive and significant effect on the quality of human resources of participants in Balai Latihan Kerja (BLK) Technopark Ganesha Sukowati Sragen. The multiple linear regressions model in this research is Y=10,278+0,117 X1+0,216 X2+0,299 X3+e. To improve the abilities and skills of each individual, they have to attend training and have work experiences, even though they have a low level of education, it does not rule out the possibility of superior quality human resources can be achieved by them. Thus, the individual is able to compete in the working world. Keywords: The quality of human resources, education level, job training, work experience